Changes in the near edge x-ray absorption fine structure of hybrid organic–inorganic resists upon exposure. (4th July 2018) - Fallica, Roberto; Watts, Benjamin; Rösner, Benedikt; Della Giustina, Gioia; Brigo, Laura; Brusatin, Giovanna; Ekinci, Yasin
Abstract: We report on the near edge x-ray absorption fine structure (NEXAFS) spectroscopy of hybrid organic–inorganic resists. These materials are nonchemically amplified systems based on Si, Zr, and Ti oxides, synthesized from organically modified precursors and transition metal alkoxides by a sol–gel route and designed for ultraviolet, extreme ultraviolet (EUV) and electron beam lithography. The experiments were conducted using a scanning transmission x-ray microscope (STXM) which combines high spatial-resolution microscopy and NEXAFS spectroscopy. The absorption spectra were collected in the proximity of the carbon edge (∼290 eV) before and after in situ exposure, enabling the measurement of a significant photo-induced degradation of the organic group (phenyl or methyl methacrylate, respectively), the degree of which depends on the configuration of the ligand. Photo-induced degradation was more efficient in the resist synthesized with pendant phenyl substituents than it was in the case of systems based on bridging phenyl groups. The degradation of the methyl methacrylate group was relatively efficient, with about half of the initial ligands dissociated upon exposure. Our data reveal that such dissociation can produce different outcomes, depending on the structural configuration. While all the organic groups were expected to detach and desorb from the resist in their entirety, a sizeable amount of them remained and formed undesired byproducts such as alkene chains. In the framework of the materials synthesis and engineering through specific building blocks, these results provide a deeper insight into the photochemistry of resists, in particular for EUV lithography.